The Impact of Starting Urate-Lowering Therapy (ULT) During A Gout Flare on The Ongoing Episode: A Systematic Review of Randomized Controlled Trials - Yogiswara, Komang Satvika; Widhiarta, Putu Raka; Wiwekananda, Ketut Shri Satya; Paramaiswari, Ayu; Achadiono, Dedy Nurwachid; Kambayana, Gede; Kertia, Nyoman (Acta Interna The Journal of Internal Medicine, 2024)
Background. Gout is a prevalent form of arthritis caused by the accumulation of monosodium urate (MSU) crystals. Urate-lowering therapy (ULT) may be started once an acute flare has subsided to prevent the present episode from lasting longer. Nevertheless, ULT may be commenced during an acute flare-up in order to decrease the frequency of outpatient appointments and enhance patient adherence. The objective of this study was to conduct whether the commencement of urate-lowering therapy (ULT) during an acute gout flare is effective. Method. We performed a systematic review of articles published in MEDLINE, PubMed, Cochrane library, and EMBASE databases from 2018 to 2023. The search was limited to articles published in English, and RCTs in patients older than 18 years.Results and Discussions. Among 242 recorded studies, only four with 323 patients were eligible for this research. The treatment with Allopurinol began with a daily dose    of 100 mg for the initial 14 days, followed by an increase to a daily dose of 200 mg for     the subsequent 14 days. The reported time to resolution was 15.4 days for the group receiving allopurinol and 13.4 days for the group receiving the placebo. According to this review, the start of ULT (uric acid-lowering therapy) should be determined by sufficient anti-inflammatory measures. Commencing ULT during a gout flare has no impact on the intensity, duration, or likelihood of recurrence of the flare within the following 28 to 30 days.Conclusions. This study demonstrated that the commencement of urate-lowering therapy (ULT) during an acute gout flare did not result in a longer duration of the flare. Nevertheless, it is necessary to conduct a clinical  studies with a bigger sample size in order to validate this review.